Implementasi kurikulum merdeka pendidikan agama Islam untuk mengasah keterampilan berpikir kritis siswa - Zulfa, Indana; Ulum, M. Bustanul (Al-Liqo: Jurnal Pendidikan Islam, 2025)
This study aims to provide a clear and in-depth picture of how the independent curriculum of Islamic Religious Education (PAI) can be a strategic means to form vocational high school graduates who are not only noble, but also think critically, adaptively, and ready to face global challenges. In this study, the data sources used were primary and secondary data sources. Data collection techniques used observation, interviews, documentation and descriptive analysis. The results of the study showed that the implementation of the independent learning curriculum showed a positive impact. Learning is centered on students with various approaches and innovations, such as project-based learning such as ppt, and other applications so that it can strengthen students' critical thinking. This is evident from the increase in students' critical thinking skills from the 2013 curriculum with a comparison of the independent curriculum carried out by teachers with an average of 80 to 85. The contribution of the independent curriculum is very significant, even though it started from some students who had minimal ability to think critically. In addition, it also improves teaching skills for Islamic Religious Education (PAI) teachers at Al-Mujahidi Plus Vocational School.